PENYULUHAN MELAHIRKAN GENERASI EMAS KEPADA MASYARAKAT DESA LUMBAN PEA TIMUR, KABUPATEN TOBA - Jekson Martiar Siahaan; Juli Jamnasi; Juli Y. Mega; Laura Octavina Siagian; Lesmana Syahrir; Lylys Surjani; Maestro B. U. Simanjuntak; Paul S. M. L. Tobing; Suryati Sinurat; Tengku M. Fauzi; Eka Samuel P. Hutasoit; Jan Pieter Sihombing; Hadyanto Lim; Hendrika A. Silitonga; Ronald T. H. Tambunan; Menang Bastanta Tarigan; Salomo G. U. Simanjuntak; Sumihar M. R. Pasaribu; Putri C. Eyanoer; Dina Riani Purba; Yohanna Agustina Sinaga (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service (PkM) is carried out by the Faculty of Medicine Universitas Methodist Indonesia by providing counselling how to prepare the Gold Generation. PkM was held on 8-11 June 2022 at Lumban Pea Timur, Balige,Toba District, North Sumatera. The method used is to provide counselling/lectures and provide motivation, then followed by question and answer to obtain results and solutions as a form of solving problems and obstacles faced. The results of PkM with counselling are very effective considering that there are still many people who do not get information about the meaning of Gold Generation. With this counselling, the public becomes aware of the Gold Generation. Thus, it is hoped that the people of Lumban Pea Timur will aware and know how to prepare the Gold Generation for their community